Advances in screening and management of unruptured intracranial aneurysms - Rinkel, Gabriel J. E.; Ruigrok, Ynte M.; Krings, Timo; Etminan, Nima; Vergouwen, Mervyn D. I. (The lancet, 2025)
The clinical evaluation and decision making associated with the management of unruptured intracranial aneurysms are complex. In the past 5 years, studies have evaluated the benefits of screening in people at high-risk, such as those with a family history of aneurysmal subarachnoid haemorrhage or unruptured intracranial aneurysms, people with genetic or other disorders associated with intracranial aneurysms, and people who smoke and have hypertension. If an aneurysm is detected during screening or incidentally, prediction models now allow for estimating the risk of complications from preventive aneurysm occlusion. Other prediction models can estimate the risk of aneurysm growth and the risk of rupture after growth. Thus, screening and management strategies are shifting towards a personalised approach. Uncertainties remain regarding the value of screening in some individuals, the long-term benefits of preventive occlusion, and the effectiveness of medical treatment strategies to prevent aneurysm growth and rupture.
Online verfügbar: 15. Oktober 2025
Gesehen am 04.12.2025